Top-down dilution of conservation commitments in Europe:An example using breeding site protection for wolves - Sazatornil, Victor; Trouwborst, Arie; Chapron, Guillaume; Rodriguez, Alejandro; Vicente Lopez-Bao, Jose (Biological Conservation, 2019)
In Europe, decision-making power related to biodiversity conservation has been partly, and voluntarily, relinquished by countries to superior levels. In this hierarchical top-down scenario, the Bern Convention and the EU Habitats Directive grant protection to a considerable number of taxa, and determine underlying conservation actions at (sub)national levels. The protection mandates emanating from these legal instruments are expected to be transferred effectively to lower levels, adapting general obligations to species-specific contexts. We assessed the implementation of general obligations from international agreements through local regulations, using as illustrative example the European requirement of protecting the breeding sites of protected species, and the conservation of grey wolves (Canis lupus) in Europe. After reviewing 43 wolf management and conservation plans across Europe, only 14% of wolf plans contained management guidelines issued to avoid wolf breeding site destruction or disturbance (this figure was 52% in the case of North America, n = 25 wolf plans). In Europe, we found only seven actions or guidelines designed to ensure breeding site protection/availability for wolves (from six countries). None of the plans contained a comprehensive set of measures to preserve breeding sites or guarantee their availability. Our results suggest that transposition of general obligations from international agreements into local legislation systems may be a critical point of weakness in the biodiversity conservation policy process. We recommend additional scrutiny to ensure that ambitious conservation goals are not diluted, but enforced, along its way from high-tier laws to local regulations, in accordance with the letter and spirit of international agreements.